Microgrid operation planning toward high reliability - Lee, Jia Yi (Nanyang Technological University, 2023)
This report investigates the operational planning of microgrids to achieve high reliability, focusing primarily on the incorporation of photovoltaic (PV) systems and battery energy storage systems (BESS). Microgrids are increasingly recognised as essential for creating sustainable and resilient energy infrastructures. The study underscores the significance of integrating PV systems, which are pivotal for renewable energy generation, and highlights the role of BESS in maintaining energy stability and providing backup power. The research meticulously examines the challenges and strategies associated with these technologies to ensure consistent power delivery and grid stability. Through a detailed examination of system modelling, control techniques, and simulation, the thesis aims to contribute to the efficient management and optimization of microgrid operations, thereby reinforcing the grid's reliability in face of growing energy demands.